Scarcity in the twenty-first century: How the resource nexus affects management - SCHILLEBEECKX, Simon J. D. (Institutional Knowledge at Singapore Management University, 2018)
Since theadvent of the 21st century and especially since the food andfinancial crisis in 2008, concerns about natural resource availability haveresurfaced. While scarcity concerns date back hundreds of years and arefoundational to economics, how scarcity is interpreted or framed has evolved significantlyin the last two centuries. In this chapter, we recount the evolving scarcity discourseand specifically address the most recent iteration that centres on the idea ofa resource nexus. While significant attention to the nexus has been paid bypolicy-makers and scholars interested in especially water, management scholarshave so far remained absent from these debates. Given recent calls to address grand challenges in management and morespecific calls for work on scarce natural resources, both this book and thischapter are timely endeavors (George et al., 2015). The munificence ofthe natural environment is an important issue for the well-being of mankind ingeneral which affects the organization of the (post-) industrial economy.Various trends are suggestive of mounting resource needs that somehow need be met.Global population growth in combination with millions of people beinglifted out of poverty following industrialization has increased pressure onnatural ecosystems as demand for energy and water-intense food crops climbs. Inconjunction with this trend, urbanization and violent conflict are driving massmigrations that challenge both natural systems and political institutions.While the human and social toll of violent conflict is evident, it isnonetheless important to recognize that for every person dying in armedconflict, about a 1,000 people die due to lack of access to clean water or as aconsequence of household air pollution.The decreasing ability of natural environments to function amidst on-going,unabated human interference is a contemporary, urgent problem. This reducedabsorption capacity is a form of resource scarcity where we still lackimportant scientific understanding. As a consequence, governments have investedin security measures and hedges to scarcity, especially when it comes to foodand energy independence, resulting in the phenomenon of land grabs as a form offoreign direct investments made by governments and sovereign wealth funds (ADB, 2013; Andrews-Speed et al., 2012; Lee et al.,2012; Xynteo, 2012). Thecombination of these and other trends poses serious challenges fororganizations that are directly or indirectly dependent on natural environments’functioning. While challenges might be more pronounced for those organizationsin the extractive industries, all organizations ought to ensure that theiremployees and community stakeholders can sustain themselves withoutexperiencing undue harm caused by the organization’s operations. In whatfollows, we first provide a short overview of the evolving scarcity framingsculminating in the current nexus approach (Allouche et al.,2015; Andrews-Speed et al., 2012; Foran, 2015; Hoff, 2011). Our review of the literature allows us topresent a framework of a multi-dimensional nexus in which source and sinkresources and the natural dynamics underlying them interact withtechno-economical, socio-political, and market processes. We then propound amanagerial approach that revolves around dynamism, munificence, and complexitywhich are central constructs in organizational theory (Anderson andTushman, 2001). Building on theoretical insights gatheredfrom prior research on organizational ecology and resource dependence theory (Hannan and Freeman,1977; Pfeffer and Salancik, 1978) as well as on current actions of companiesto deal with nexus problems, we propose complementary strategies that can beused as nexus management strategies in a hyper-connected world.